Axial p–n junction and space charge limited current in single GaN nanowire. (29th November 2017) - Fang, Zhihua; Donatini, Fabrice; Daudin, Bruno; Pernot, Julien
Abstract: The electrical characterizations of individual basic GaN nanostructures, such as axial nanowire (NW) p–n junctions, are becoming indispensable and crucial for the fully controlled realization of GaN NW based devices. In this study, electron beam induced current (EBIC) measurements were performed on two single axial GaN p–n junction NWs grown by plasma-assisted molecular beam epitaxy. I – V characteristics revealed that both ohmic and space charge limited current (SCLC) regimes occur in GaN p–n junction NW. Thanks to an improved contact process, both the electric field induced by the p–n junction and the SCLC in the p-part of GaN NW were disclosed and delineated by EBIC signals under different biases. Analyzing the EBIC profiles in the vicinity of the p–n junction under 0 V and reverse bias, we deduced a depletion width in the range of 116–125 nm. Following our previous work, the acceptor N a doping level was estimated to be 2–3 × 10 17 at cm −3 assuming a donor level N d of 2–3 × 10 18 at cm −3 . The hole diffusion length in n-GaN was determined to be 75 nm for NW #1 and 43 nm for NW #2, demonstrating a low surface recombination velocity at the m -plane facet of n-GaN NW. Under forward bias, EBIC imaging visualized the electric field induced by the SCLC close to p-side contact, in agreement with unusual SCLC previously reported in GaN NWs.